Illegal building problems in Selangor / Siti Nurfarahin Mohamad Ghazali - Mohamad Ghazali, Siti Nurfarahin (Faculty of Architecture, Planning and Surveying, 2013)
Local authority has a power to manage the construction development. The authority has a role in planning permission and gives the plan approval. Every construction cannot be done without the permission from local authority. In local authority, the Department of Building Control will be managed the procedures and process of approval plan and permission. Any new construction or alterations for existing building, there are need the permission from local authority. Building plan should be detail with drawing, specification, material use, location plan and so on. Any building that construct from get the permission from local authority, the building will be declared as an illegal building. Illegal building is a building that be construct by owner without the approval and permission from local authority. The problem statement for this research is building be construct without the permission from local authority, illegal building can causes the problems for development planning, how local authority overcome the issue of illegal building and the issue of amended plan without obtaining approval from local authority. The objectives for this research is to identify the seriousness of illegal building problems, to identify problems faced by local authority in overcoming illegal building and to appraise different approaches to overcome illegal building by local authority. The cases studied will be conducted at three local authorities in Selangor area. This research will be used the interview session and literature review to collect the data information of illegal building. The methodology for this research by using the interview to the experienced officer at local authority, observation of previous cases of illegal building and some literature review. The main findings of this research is the action of local authority for the building owner, to know how local authority manages the issue of illegal building and what the alternatives that had been done by local authority in handle the issue of illegal building.